Video Game Addiction and its Relationship with Sleep Quality among Medical Students - Faisal Ahmed Dakheel-allah Alghamdi; Faisal Ahmed Ghanim Alghamdi; Abdullah Abusulaiman; Abdulaziz Jabr Alsulami; Mohammed Bamotref; Albraa Alosaimi; Omar Bamousa; Siraj Omar Wali (Springer, 2024)
Abstract Background Although many health problems, including sleep disorders, have been associated with video gaming, further studies are required to establish the validity of these connections. This study aimed to determine the prevalence of gaming addiction among medical students and its association with poor sleep quality, which may be reflected in academic performance. Method A cross-sectional survey was conducted between January and June 2023 among medical students at the institution under study. An online survey was conducted and was divided into three sections. The first section included the demographic data, the second section included the 7-item Gaming Addiction Scale (GAS), and the third section included the Pittsburgh Sleep Quality Index. Using the GAS, and based on the total score, gamers were classified as addicted, problematic, engaged, or normal. Hence, abnormal gamers include engaged, problematic, and addicted gamers. Result There were 356 participants with a mean age of 22.5 -/+ 1.8 years, and 75.3% were males. The data showed that 38.8% of the study population were abnormal gamers: 40 (11.2%) engaged gamers, 81 (22.8%) problematic gamers, and 17 (4.8%) addicted gamers. Furthermore, abnormal gaming was linked to poor sleep quality when comparing abnormal gamers with normal gamers (92% vs. 80.3%, p = 0.002). Further comparison between the types of abnormal gamers revealed that addicted gamers were found to rely on sleep medication to help them sleep at night and took longer time to fall asleep (p = 0.050 and p = 0.045, respectively). Conclusion Abnormal gamers are common among medical students and strongly associated with poor sleep quality compared to normal gamers.